2014
DOI: 10.1021/pr401068k
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy-Induced Metabolic Phenotype Variations in Maternal Plasma

Abstract: Metabolic variations occur during normal pregnancy to provide the growing fetus with a supply of nutrients required for its development and to ensure the health of the woman during gestation. Mass spectrometry-based metabolomics was employed to study the metabolic phenotype variations in the maternal plasma that are induced by pregnancy in each of its three trimesters. Nontargeted metabolomics analysis showed that pregnancy significantly altered the profile of metabolites in maternal plasma. The levels of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 40 publications
7
76
1
Order By: Relevance
“…This leads to increased stores during the first trimester, followed by enhanced release and increased levels of circulating nutrients in the last part of pregnancy, corresponding to exponential fetal growth. A recent trial analyzed the metabolic phenotype variations in maternal plasma of 180 healthy pregnant women, using a metabolomics approach in the three trimesters [12]. Nontargeted metabolic profiling analysis showed a profound alteration in the macronutrient metabolic phenotype with a statistically significant separation between trimesters mainly due to amino acid and lipid metabolism [12].…”
Section: Nutritional Phenotype Of Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to increased stores during the first trimester, followed by enhanced release and increased levels of circulating nutrients in the last part of pregnancy, corresponding to exponential fetal growth. A recent trial analyzed the metabolic phenotype variations in maternal plasma of 180 healthy pregnant women, using a metabolomics approach in the three trimesters [12]. Nontargeted metabolic profiling analysis showed a profound alteration in the macronutrient metabolic phenotype with a statistically significant separation between trimesters mainly due to amino acid and lipid metabolism [12].…”
Section: Nutritional Phenotype Of Pregnancymentioning
confidence: 99%
“…A recent trial analyzed the metabolic phenotype variations in maternal plasma of 180 healthy pregnant women, using a metabolomics approach in the three trimesters [12]. Nontargeted metabolic profiling analysis showed a profound alteration in the macronutrient metabolic phenotype with a statistically significant separation between trimesters mainly due to amino acid and lipid metabolism [12]. These metabolic changes are demonstrable even for micronutrients.…”
Section: Nutritional Phenotype Of Pregnancymentioning
confidence: 99%
“…Substantially, these physiological variations come from the metabolic changes during the pregnant period (King, 2000;Luan et al, 2014), which are complex and widespread, resulting in the maternal metabolism working from a different baseline compared with the non-pregnant state. Among the reported changes, those in amino acid metabolism, energy and gut microflora metabolisms were observed in connection to pregnancy (Pinto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbohydrate metabolism received particular concerns due to the wellrecognized clinical disorder known as diabetes mellitus (Hernandez et al, 2014). Recently, an untargeted metabolomics analysis with LC-MS and shotgun lipidomics of maternal plasma showed that the levels of dihydrobiopterin (BH 2 ), carnitine, acetylalanine, leucyl-phenylalanine, lysophosphatidylcholine (LPC) (18:1), and LPC (20:4), were found to change significantly throughout pregnancy, as well as the changes in the total concentrations of LPCs, phosphatidylcholines (PHCs), lysophosphatidylethanolamines (LPEs) and lysophosphatidylserines (LPSs) (Luan et al, 2014). Meanwhile, the dynamic metabolic adaptations of maternal urine from healthy pregnancies has been evaluated by NMR-based metabolomics techniques, in which the levels of 21 metabolites including choline, creatinine, 4-deoxyerythronic acid, 4-deoxythreonic acid, furoylglycine, guanidoacetate, 3-hydroxybutyrate, and lactate were found to change significantly throughout pregnancy (Diaz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a controlled experiment involved QC samples throughout the data collection process, the most advantageous uses of QC samples can be obtained, allowing the correction of signal drift and other systematic noise through mathematical algorithms in liquid or gas chromatography (LC or GC) hyphenated to MS-based metabolomics study 5,6 . However, there is few such controlled experiment and algorithms for improving the data quality in label-free LC-MS based proteomics 4,7 .…”
Section: Introductionmentioning
confidence: 99%